Primary Skin Closure after Repair of Hollow Viscus Injuries. Issue 10 (October 2019) - Holloway, Janell; Lett, Lanair Amaad; Marcia, Lobsang; Putnam, Brant; Neville, Angela; Patel, Neil; Chong, Vincent; Kim, Dennis Y.
Decisions regarding whether to close the skin in trauma patients with hollow viscus injuries (HVIs) are based on surgeon discretion and the perceived risk for an SSI. We hypothesized that leaving the skin open would result in fewer wound complications in patients with HVIs. We performed a retrospective analysis of all adult patients who underwent operative repair of an HVI. The main outcome measure was superficial or deep SSIs. Of 141 patients, 38 (27%) had HVIs. Twenty-six patients developed SSIs, of which 13 (50%) were superficial or deep SSIs. On adjusted analysis, only female gender ( P = 0.03) and base deficit were associated ( P = 0.001) with wound infections Open wound management was not associated with a decreased incidence of SSIs ( P = 0.19) in patients with HVIs. Further research is required to determine optimal strategies for reducing wound complications in patients sustaining HVIs.